Implementasi Pemikiran Filosofis Paulo Freire dalam Dunia Pendidikan - Eman Sulaeman (Sekolah Tinggi Agama Islam Persatuan Umat Islam Majalengka, 2025)
This study aims to analyze the application of Paulo Freire's philosophical thought in education and its relationship to the principles of Islamic education and the educational context in Indonesia. According to Freire, education should be a liberation pedagogy that develops critical awareness (conscientization) through dialogue, reflection, and concrete action (praxis). However, education in Indonesia is still dominated by a conventional paradigm that positions students as passive objects. This study uses library research with a qualitative-descriptive approach, through an analysis of Freire's works, Islamic education literature, and national education policy documents. The results reveal that Freire's main principles—such as dialogical education, humanization, critical awareness, and social transformation—correlate with Islamic values ??such as tafakkur (religious reflection), syura (compassion), tazkiyah an-nafs (compassion for the self), and justice ('adl). In the context of Indonesian education, Freire's ideas are reflected in the implementation of the Merdeka Curriculum, which emphasizes active, reflective, and participatory learning. However, the main challenges remain related to the hierarchical teacher paradigm and a bureaucratic system that does not fully support a humanistic approach. This study concludes that the application of Freire's thinking has the potential to become the foundation for transforming education in Indonesia toward a system that is just, empowering, and based on divine values.